2009
DOI: 10.1002/qua.560070731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison for pyrrole and pyrazole of orbital energies and population analyses from ab-initio SCF, CNDO/2, INDO, extended hückel, and ARCANA calculations

Abstract: The results of our recent ab-initio SCF calculations on pyrrole and pyrazole using large Gaussian basis sets are compared to those using less rigorous methods: CNDO/2. INW. PCILO extended Hiickel, and ARCANA (a type of iterative extended Hiickel calculation). The ab-initio orbital energies are higher in energy than all those resulting from less rigorous methods. For the two highest occupied orbitals, both of n type, (pyrrole-la, and 2b, ; pyrazole-3a" and 2a") there was excellent agreement between the measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The hydrogens bear a good part of the excess positive charge. In accord with our earlier findings about the nonagreement of C N D O /~ electron densities with those from good ab initio LCAO-MO-SCF calculations [34], we consider of primary significance the fact that comparison of our CNDO/2 electron densities on the N of the free base narcotic (or narcotic antagonist) show them to differ only by a small fraction ( -0.2) of an electronic charge from the CND0/2 calculated electron density in the respective protonated form. We would attach only secondary significance to the magnitudes (and even sometimes the signs) of the C N D O /~ calculated charges.…”
Section: W Ithout Opt Imizat Ion Of Polaritiessupporting
confidence: 90%
See 1 more Smart Citation
“…The hydrogens bear a good part of the excess positive charge. In accord with our earlier findings about the nonagreement of C N D O /~ electron densities with those from good ab initio LCAO-MO-SCF calculations [34], we consider of primary significance the fact that comparison of our CNDO/2 electron densities on the N of the free base narcotic (or narcotic antagonist) show them to differ only by a small fraction ( -0.2) of an electronic charge from the CND0/2 calculated electron density in the respective protonated form. We would attach only secondary significance to the magnitudes (and even sometimes the signs) of the C N D O /~ calculated charges.…”
Section: W Ithout Opt Imizat Ion Of Polaritiessupporting
confidence: 90%
“…it was obvious that these were not optimal physical structures.) (Comparison of gross atomic populations corresponding to electron densities calculated by the C N D O /~ and INDO methods with those resulting from ab initio calculations on pyrrole and pyrazole [33] showed that there were notable discrep ancies in the resulting molecular charge distributions calculated by C N D O /~ and INDO methods [34]. However, calculated differences in closely related congeners hopefully should reflect realistically the differences in molecular charge distributions.)…”
Section: Quantum Chemical and Physicochemical Resultsmentioning
confidence: 95%